2019
DOI: 10.3390/ijerph16224519
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Applying Statistical Disclosure Control Methods to Public Health Research

Abstract: Patient data or information collected from public health and health care surveys are of great research value. Usually, the data contain sensitive personal information. Doctors, nurses, or researchers in the public health and health care sector do not analyze the available datasets or survey data on their own, and may outsource the tasks to third parties. Even though all identifiers such as names and ID card numbers are removed, there may still be some occasions in which an individual can be re-identified via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Non‐confidential data can be age and years of work experience of customers. Another example of confidential variables is from 12 where we see the responses to five sleep‐related questions in a clinical trial regarded as confidential, and height and weight of participants in the clinical trial taken as non‐confidential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐confidential data can be age and years of work experience of customers. Another example of confidential variables is from 12 where we see the responses to five sleep‐related questions in a clinical trial regarded as confidential, and height and weight of participants in the clinical trial taken as non‐confidential.…”
Section: Methodsmentioning
confidence: 99%
“…Reference 11 developed and released an open R package synthpop to public and businesses for their easy generation of synthetic data. Apart from business applications, some examples of recent applications of SDC methods to healthcare data and research can be found in References 12,13. An interesting application of SDC methods to healthcare research can be found in Reference 14, which introduces a method to produce synthetic medical image data to allow more patient data to be used without privacy concerns.…”
Section: Introductionmentioning
confidence: 99%